2021
DOI: 10.3390/cancers13112624
|View full text |Cite
|
Sign up to set email alerts
|

Dynein Light Chain Protein Tctex1: A Novel Prognostic Marker and Molecular Mediator in Glioblastoma

Abstract: The purpose of this study was to determine the role of Tctex1 (DYNLT1, dynein light chain-1) in the pathophysiology of glioblastoma (GBM). To this end, we performed immunohistochemical analyses on tissues from GBM patients (n = 202). Tctex1 was additionally overexpressed in two different GBM cell lines, which were then evaluated in regard to their proliferative and invasive properties. We found that Tctex1 levels were significantly higher in GBM compared to healthy adjacent brain tissues. Furthermore, high Tct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…With the development of modern genomic/transcriptomic technologies and increasing public cancer genomic programs, such as TCGA and GEO, numerous biomarkers were identified for improving our ability to diagnose and treat cancer or utilized as predictors of prognosis and response to therapies in cancer. For example, DYNLT1 serving as a prognostic indicator for GBM patients has been reported ( 12 ). However, there is no report on whether DYNLT1 may act as a biomarker of BC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the development of modern genomic/transcriptomic technologies and increasing public cancer genomic programs, such as TCGA and GEO, numerous biomarkers were identified for improving our ability to diagnose and treat cancer or utilized as predictors of prognosis and response to therapies in cancer. For example, DYNLT1 serving as a prognostic indicator for GBM patients has been reported ( 12 ). However, there is no report on whether DYNLT1 may act as a biomarker of BC.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that DYNLT1 plays an important role in many biological functions and diseases, such as Huntington's disease ( 8 ), fertilizing potential of human spermatozoa ( 9 ), migration of epidermal cells in hypoxia ( 10 ), autophagy lysosomal degradation ( 11 ), and several types of cancer. DYNLT1 has been reported to promote glioblastoma progression and is associated with tumor-node-metastasis (TNM) grade ( 12 ). In gastric cancer (GC), DYNLT1 takes part in the miR-15b-3p/Caspase-3/Caspase-9 signaling pathway to promote malignant transformation ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…TMA blocks were built using the Arraymold kit E (Riverton, UT, USA) as previously described [ 54 , 55 ] and cut into 2 µm sections. The sections were incubated with 667 ng/mL PLOD2-specific polyclonal antibodies (Proteintech Europe, Manchester, UK) or 500 ng/mL anti-human CD66b antibodies (BioLegend, San Diego, CA, USA) at 4 °C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…TMAs were constructed and stained as previously described [22,23]. The following primary antibodies were used: 112 ng/mL monoclonal rabbit anti-PGRMC1 (Cell Signaling Technology, Frankfurt am Main, Germany), 3.6 µg/mL polyclonal rabbit anti-Integrin beta-1 (Proteintech Europe, Manchester, UK), and 0.66 µg/mL monoclonal mouse anti-CD66b (BioLegend, San Diego, CA, USA).…”
Section: Tissue Microarrays (Tma): Immunohistochemistry and Scoringmentioning
confidence: 99%